2018
DOI: 10.1002/jnr.24378
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of cerebellar afferent and efferent pathways in a healthy right‐handed population: A diffusion tensor imaging study

Abstract: The cerebellum communicates with the cerebral cortex through the cortico‐ponto‐cerebellar tract (CPCT, cerebellar afferent) and the dentato‐rubro‐thalamo‐cortical tract (DRTCT, cerebellar efferent). This study explored the laterality of CPCT and DRTCT in a right‐handed population. Forty healthy right‐handed subjects (18 males and 22 females with age range of 26–79 years old) who underwent diffusion tensor imaging (DTI) were retrospectively enrolled. Bilateral CPCT, DRTCT, and the corticospinal tract (CST) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 57 publications
1
27
0
1
Order By: Relevance
“…Commonly, the DNs are known to be involved in sensorimotor processes but recent functional imaging investigations have revealed that they play a role also in non‐motor functions (Alahmadi et al, 2017 ; Bharti et al, 2020 ; Habas, Guillevin, & Abanou, 2011 ; Zhang et al, 2015 ). This finding is in line with the recent understanding that the cerebellum is connected to cognitive and associative cortical areas, as supported by either tract‐tracing techniques (Kelly & Strick, 2003 ; Middleton & Strick, 1994 ; Schmahmann & Caplan, 2006 ; Schmahmann & Pandya, 1995 ; Strick, Dum, & Fiez, 2009a ) or diffusion MRI tractography studies of the cerebro‐cerebellar loop (Kim, Im, Kim, & Park, 2019 ; Palesi et al, 2015 , 2016 , 2017 ).…”
Section: Introductionsupporting
confidence: 86%
“…Commonly, the DNs are known to be involved in sensorimotor processes but recent functional imaging investigations have revealed that they play a role also in non‐motor functions (Alahmadi et al, 2017 ; Bharti et al, 2020 ; Habas, Guillevin, & Abanou, 2011 ; Zhang et al, 2015 ). This finding is in line with the recent understanding that the cerebellum is connected to cognitive and associative cortical areas, as supported by either tract‐tracing techniques (Kelly & Strick, 2003 ; Middleton & Strick, 1994 ; Schmahmann & Caplan, 2006 ; Schmahmann & Pandya, 1995 ; Strick, Dum, & Fiez, 2009a ) or diffusion MRI tractography studies of the cerebro‐cerebellar loop (Kim, Im, Kim, & Park, 2019 ; Palesi et al, 2015 , 2016 , 2017 ).…”
Section: Introductionsupporting
confidence: 86%
“…Exclusion criteria were: (1) recurrent stroke; (2) diagnosis of brain complications after stroke, such as hydrocephalus; (3) underlying degenerative brain disease, such as Parkinson’s disease; and (4) other pain syndrome, such as complex regional pain syndrome, fibromyalgia, or other rheumatologic disease. Normal controls were age- and sex-matched subjects chosen from the data from the Health Promotion Center of our institution [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, cortico-ponto-cerebellar system microstructural changes have been related to memory impairment in ALS patients, ( Trojsi et al, 2020 )., Mean FA of the CPT was reduced in ALS patients in a longitudinal multicenter study ( Kalra et al, 2020 ). The CPT is associated with hand dominance-related alterations ( Kim et al, 2019 ). In addition, previous researches have demonstrated that the integrity of the CPT in patients with chronic stroke affects the residual upper limb function ( Schulz et al, 2015 ; Guder et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%